English Proficiency Evaluation Model of College Students by Using Intuitive Fuzzy Information Theory - Tang, Dongdong (Advances in Multimedia, 2022)
English is a required university course in China and is a long-standing and consistent undergraduate-level course in China’s universities. It uses English as the medium and language of instruction to promote general education. As the most important content of undergraduate foreign language education, college English has different characteristics from other courses. It is only when its objectives, content, teaching activities, and assessment system fully reflect its unique requirements that it can truly achieve the ultimate goal of teaching this subject. With the advent of the information age, global economic integration and international exchange are deepening in various industries and fields. It is increasingly common for countries to require professionals to have foreign language skills, especially English as an international language. As a result, the demand for deeper English proficiency has become more prominent. In international communication, the English intercultural communication ability of key personnel directly affects the process of international communication, science and technology exchange, and the smooth transition of cultural conflicts in various fields and even determines the ultimate success of project cooperation. In this context, the effective use of English and cross-cultural communication skills is very important. Therefore, our higher education institutions are mainly responsible for training foreign language talents. However, the core problem facing English teaching in Chinese universities is the teaching value orientation. In particular, it seriously restricts the effectiveness of university English teaching. First, the value orientation of university English teaching deviates from the teaching objectives. It emphasizes the basic knowledge and skills of the English language, which makes teaching mainly stay on the foundation of the language. In other words, it is still limited to learning English for the sake of learning English, and the examination-oriented education is obvious, with a preference for instrumental teaching. Secondly, university English teaching focuses too much on the accumulation of English grammar rules and imitation drills, and the teaching style is dull and the teaching context is empty. This approach deviates from the characteristics of English intercultural communication, which makes the gap between the actual university English teaching and the real intercultural communication more and more obvious. Third, university English teaching lacks integration with other teaching values, especially with the humanistic orientation of university English teaching. Nowadays, a single teaching value orientation dominates university English teaching. As a result, the teaching around various English examinations has become a strange phenomenon in college English teaching.